Sexual and reproductive health among young persons' with disability in six districts of Nepal. - Gaihre,Ramchandra (2015)
SUMMARY: This research was designed to gain a contextual understanding of the factors affecting and, to explore the level of awareness and utilization of Sexual and Reproductive Health (SRH) services among young persons with disability in six districts of Nepal. This report only covers the quantitative part of the study, which mainly focuses on awareness, utilization of Family Planning (FP) and Safe Abortion (SA) services, STI prevention, and perceived barriers faced by YPWD in accessing SRH services. This was conducted to gain better understanding regarding the SRH needs of YPWD such that programs can be implemented which focuses on increasing access to SRH services in MSI-Nepal's youth project districts. The study districts- Kathmandu, Lalitpur, Bhaktapur, Kaski, Parsa and Morang were purposively selected based on the large proportion of youth with disabilities, and also because they have youth-friendly Marie Stopes Center for future referral to our study participants. Within the study districts samples were selected using multi-stage sampling. From each study site a disabled person's organization (DPO) was randomly selected. A focal person from the selected organization was recruited to advice on initial approach to seed sample selection and identification. Prospective participants were then approached through snowball sampling until the required sample size was obtained. Research assistants with similar types but minor degree of disability were recruited and trained intensively for data collection. A total of 293 married and unmarried young men and women, aged 15-30 years, with one of three types of disability (deaf, blind or physical) were recruited. Those with multiple disabilities were excluded. After giving voluntary written informed consent (and assent when required), respondents completed a pre-tested structured questionnaire administered by trained Research Assistants (RAs). The Nepal Health Research Council gave ethical clearance and approval for the study. Descriptive analyses were performed in SPSS v22 to quantify distributions of discrete and continuous variables. The key results from the study are as follows: Demographic Profile  55% male and 46.1% female with disability participated in this survey.  45.7% of the respondents had physical disability while 22.5% were hard of hearing including deaf and 31.7% were blind or had low vision.  The mean age of the respondents was 23.6 years (±4 years) and 10.2% had either no formal education or some primary education only.  72.7% of the respondents were single. Among those who are currently married, 91.4% reported of living with their spouses at the time of data collection.  60.9% of the respondent's spouses/partners had some kind of disability. Awareness on Sexual and Reproductive Health and Rights  95% of the respondents had heard about family planning. Condoms (85.7%) followed by injectables (65.9%) were the most popular methods. Interestingly, 68.9% had heard about emergency contraceptives. Hospitals (both government and private including nursing homes and clinic), health post and pharmacies were the most know places to obtain FP method and counseling.  94% of the respondents had heard about safe abortion services. Among them 61% were aware that SA service is legal in Nepal. Furthermore, 59% of the respondents reported that they knew about different methods of SA services. Medical abortion was the most known method of SA services.  91% of the respondents were aware about sexually transmitted infection with HIV/AIDS being the most recognized STI. Among them majority knew at least one correct method of preventing STI with use of condoms reported by 86.1%. However, 20.6% still had at least one misconception about STI preventions like use of oral pills, withdrawal during intercourse etc.  79.5% of the respondents had at least one or more misconception or believed in myths about family planning and safe abortion. Only 36.86% disagreed that having sex before marriage is wrong. Practice or uptake of SRHR information and services  66.6% of the respondents had ever discussed sex with anyone.  47.1% of the respondents had ever engaged in any sexual activity. The mean age of first sex was 19.7 years. 11% of the respondents who had ever had sex reported their first sex a forced one.  41.9% had had more than 1 sexual partner.  70% of the respondents who had ever had sex reported to currently using one of the methods of contraceptives. Amongst those married, 35% were not using any method of modern FP due to reasons such as fear of side effects and husband/self did not like the methods. Condoms were the most used method of contraception (68.8%) followed by traditional methods like withdrawal (18.8%) and rhythm method (7.3%). Interestingly, 4.2% using emergency contraception as their method of family planning. Pharmacies and government health facilities were the most sought after places for contraception.  Two-thirds of the respondents' decision to use or not use any method of family planning was made jointly between the respondent and their partner.  48% of the respondents did not receive any information regarding their bodily changes during adolescence. But among those who did, friends and teachers were the most popular sources.  63.9% of the females use commercial disposable pads and 90.15% sleep on their own bed during their menstruation.  82% of the respondents had heard about masturbation. Radio/TV was the most common source of information.  14% of the respondents who had ever had sex reported using safe abortion services. Medical abortion was the most used method. Avoidance of shame and fear of parents were the most cited reason for utilizing safe abortion services. Access and barriers to utilizing SRHR information and services  75.4% of the respondents reported that the nearest service center providing SRHR information and services was less than 30 minutes away. 43% said they walked to the nearest service center.  Only 38% of the respondents said that they perceived the nearest service center to be disability friendly.  Provision of physical facilities like ramps/ railings/ elevators, suitable toilets were the most mentioned aspects for a service center to be called disability friendly.  Furthermore, availability of sign language interpreters, provision of written text, IEC in Braille or large text, centers located in ground floor with ample moving space etc. were other aspects to be considered for a service centers to be accessible and disability friendly.  22% of the respondents reported difficulty in communicating with the service providers.  TV, radio as well as inter-personal communication were stated as being their preferred platform for receiving SRHR information The finding sheds an important insight on perceived barriers among YPWD in utilizing and accessing SRH services, mainly FP, which will inform program and policies to meet the needs of this group. Majority of YPWDs were unaware of comprehensive FP methods and myths and misconception were associated with FP .Disabled friendly IPC intervention should be developed to effectively deliver FP information, for instance, developing IEC materials in Braille, using sign language in mass media. Young community leaders should be involved to increase the groups' understanding of the benefits and necessities of FP. Mass media such as jingles and street drama can also increase FP awareness and shape their behavior and attitudes. This study also highlights that lack of access to service centers as physical infrastructures that are not disability friendly was a key perceived barrier. Additionally, unavailability of sign interpreter and same sex provider coupled with perceived lack of understanding of YPWD needs among service provider were other reported barriers. In response to this, Government of Nepal, including organizations working in the field of SRHR needs to have provision for disability friendly services in health facilities. As the barriers are varied by type of disability, close consultation with YPWD on disability friendly environment in the health facilities would ensure such environment in local context.